Measurement of the top-quark mass in $t\bar{t}$ events with lepton+jets final states in $pp$ collisions at $\sqrt{s}=7$ TeV - CMS collaboration (2199 authors) (2012)
The mass of the top quark is measured using a sample of t t-bar candidate events with one electron or muon and at least four jets in the final state, collected by CMS in pp collisions at sqrt(s) = 7 TeV at the LHC. A total of 5174 candidate events is selected from data corresponding to an integrated luminosity of 5.0 inverse femtobarns. For each event the mass is reconstructed from a kinematic fit of the decay products to a t t-bar hypothesis. The top-quark mass is determined simultaneously with the jet energy scale (JES), constrained by the known mass of the W boson in q anti-q decays, to be 173.49 +/- 0.43 (stat.+JES) +/- 0.98 (syst.) GeV.